Expression and Localization of DDX3 in Prostate Cancer Progression and Metastasis - Vellky, Jordan E. (Am J Pathol, 2019)
Survival rates decrease significantly when localized prostate cancer (CaP) becomes metastatic, emphasizing the need for improved targeted therapies. DDX3, an RNA helicase, has widespread functions in RNA regulation, in both the nucleus and cytoplasm. Although DDX3 has been implicated as a prognostic marker for many cancers, including primary CaP, its expression, localization, and function in metastatic CaP have not been investigated. Analysis of metadata and cell line models found increased DDX3 expression in metastatic versus primary CaP and benign prostate. Quantification of DDX3 expression in 320 human prostate samples, representing different stages of CaP progression, revealed an increase in epithelial whole cell, cytoplasmic, and nuclear DDX3 in primary CaP compared with benign prostate. In metastatic tissues, cytoplasmic DDX3 remained highly expressed, whereas nuclear DDX3 significantly decreased compared with primary CaP, suggesting a potential role for cytoplasmic DDX3 in metastatic CaP. Genetic and pharmacologic loss of function for DDX3 in metastatic CaP produced a significant decrease in cell viability, proliferation, and motility but did not affect apoptosis. The data suggest that cytoplasmic DDX3 is highly expressed in metastatic CaP and that inhibition of DDX3 affects metastatic growth by decreasing proliferation and motility. These findings introduce a novel role for cytoplasmic DDX3 in CaP progression and provide a foundation for clinically targeting DDX3 in metastatic CaP.